Analysis Of The Philosophy Of Life Of The People Of Lampung As Enrichment In Character Education In History Subjects At Sma Negeri 1 Kibang For The 2020/2021 Academic Year - Achmad Didik Khoirudin; Hermanu Joebagio; Sariyatun Sariyatun (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Learning must be a vehicle for the holistic growth and development of students' potentials through their active role towards a better chance. One of the subjects that have content of character education is History education. These characters will shape motivation with dignified methods and processes. It turns out that these character values are embodied in the philosophy of life of the people of Lampung. How is the analysis of the philosophy of life of the people of Lampung as enrichment in character education in history subjects at SMA Negeri 1 Kibang? The purpose of this study was to determine the analysis of the philosophy of life of the people of Lampung as enrichment in character education in history subjects at SMA Negeri 1 Kibang for the academic year 2020/2021. This research uses descriptive qualitative research methods with a case study approach. In teaching and learning activities there is an interaction between students regarding the subject matter. After the lesson is completed, the objectives of the analysis of Lampung's philosophical values will be achieved as an enrichment of character education, namely the inculcation of Lampung philosophical values such as Piil pesenggiri, meeting nyimah, nengah nyapur, sakai sambayan, and bejuluk adek. In history lessons, there are also aspects of character that are dominant in history learning, even though all values can be included in each subject, namely eighteen indicators of character education.